David Wong's Interpretation of Confucian Moral Psychology. - Seok, Bongrae (Dao: A Journal of Comparative Philosophy, 2017)
The article presents author's information on interpretations of author David Wong on moral psychology and Confucian self-cultivation. Topics discussed include importance of mindfulness meditation and deliberate regulation; implicit behavior of Confucian philosophers; and support of cognitive compatibility.